Google Classroom-Based Literacy Training E-Modules to Improve Teachers' Ability to Implement the School Literacy Movement - Hikinda, Fransina; Satyawati, Sophia Tri; Waruwu, Marinu (Journal for Lesson and Learning Studies, 2024)
Effective management of the School Literacy Movement (GLS) can create a literate culture of school members and improve students' literacy skills. However, in reality, the implementation of GLS in schools cannot be carried out according to the objectives of GLS because of the obstacles faced by teachers. One of them is that teachers do not understand the stages and technical implementation of GLS well. This development research aims to develop a Google Classroom-based GLS management training module for junior high school teachers. This type of research is Research and Development (RND) research using the ADDIE model approach. The subjects in this study consisted of material expert validators, ICT experts, principals and teachers. Data collection techniques were carried out using interviews, observations, documentation studies, questionnaires and tests. Data analysis techniques were carried out using mixed methods. Qualitative data was analyzed using the Milles and Huberman model and quantitative data was analyzed using descriptive quantitative and T-test. The product of this research is the Google Classroom-based literacy training E-module. The results of product testing by expert validation and prospective users in the module product trial were in the category of feasible and effective for use in GLS management training. Through this training module, it is expected that teachers can learn and utilize it as a guide in carrying out GLS activities that are more varied and have an impact on improving students' literacy competencies.